2013
DOI: 10.1093/mnras/stt1195
|View full text |Cite
|
Sign up to set email alerts
|

Hall equilibria with toroidal and poloidal fields: application to neutron stars

Abstract: We present solutions for Hall equilibria applicable to neutron star crusts. Such magnetic configurations satisfy a Grad-Shafranov-type equation, which is solved analytically and numerically. The solutions presented cover a variety of configurations, from purely poloidal fields connected to an external dipole to poloidal-toroidal fields connected to an external vacuum field, or fully confined within the star. We find that a dipole external field should be supported by a uniformly rotating electron fluid. The en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 62 publications
7
111
0
Order By: Relevance
“…corresponds to a Hall equilibrium, and will not evolve in the limit of zero resistivity (Cumming et al 2004;Gourgouliatos et al 2013;Fujisawa & Kisaka 2014). In the realistic case of non-zero resistivity, however, the system will start evolving and may be pushed out of Hall equilibrium (Marchant et al 2014).…”
Section: Electron-mhd Formulation In Neutron Star Crustsmentioning
confidence: 99%
“…corresponds to a Hall equilibrium, and will not evolve in the limit of zero resistivity (Cumming et al 2004;Gourgouliatos et al 2013;Fujisawa & Kisaka 2014). In the realistic case of non-zero resistivity, however, the system will start evolving and may be pushed out of Hall equilibrium (Marchant et al 2014).…”
Section: Electron-mhd Formulation In Neutron Star Crustsmentioning
confidence: 99%
“…Several authors (Lander & Jones 2009;Ciolfi et al 2009;Fujisawa et al 2012;Gourgouliatos et al 2013) have explored the possible axially symmetric equilibria in barotropic stars, generally finding that the fraction of the total magnetic energy corresponding to the toroidal component, E tor /E mag , is at most a few %. In addition to not being enough to account for the energy emitted by magnetars, this would be insufficient to stabilize the poloidal component (Braithwaite 2009;Akgün et al 2013), as confirmed by the simulations of Lander & Jones (2012).…”
Section: Overviewmentioning
confidence: 99%
“…We have obtained Hall equilibrium states (see Gourgouliatos et al 2013) using Green function method with arbitrary current sheets (see Fujisawa & Eriguchi 2013). For simplicity, we divided the magnetized neutron star interior into three regions in order to include the boundary conditions systematically.…”
Section: Resultsmentioning
confidence: 99%
“…Goldreich & Reisenegger 1992). Recently, Hall MHD numerical simulations (Kojima & Kisaka 2012, Viganò et al 2013 and Hall equilibrium states (Gourgouliatos et al 2013) have been calculated. Since the boundary conditions are very important in both cases, we have calculated the Hall equilibria within the neutron star crust under various boundary conditions in order to investigate the influences of the boundary conditions.…”
Section: Introductionmentioning
confidence: 99%